The handbook of juvenile delinquency and juvenile justice - Krohn, Marvin D.; Lane, Jodi 1967- (Wiley handbooks in criminology and criminal justice, 2015)
This handbook is an up-to-date examination of advances in the fields of juvenile delinquency and juvenile justice that includes interdisciplinary perspectives from leading scholars and practitioners. It examines advances in the fields of juvenile delinquency and juvenile justice with interdisciplinary perspectives from leading scholars and practitioners; provides a current state of both fields, while also assessing where they have been and defining where they should go in years to come and addresses developments in theory, research, and policy, as well as cultural changes and legal shifts. Also, it contains summaries of juvenile justice trends from around the world, including the US, the Netherlands, Brazil, Russia, India, South Africa, and China and covers central issues in the scholarly literature, such as social learning theories, opportunity theories, criminal processing, labeling and deterrence, gangs and crime, community-based sanctions and reentry, victimization, and fear of crime--